HISTORY OF ANCIENT ARCHIVES OF CENTRAL ASIA (Scientific journal of the Fergana State University, 2026)
The article analyzes the emergence, development and transformation of writing in Central Asia, the use of writing in office work and record keeping, the emergence of office work, registration of documents, their types and forms of record keeping and early archives in Central Asia, in particular in Uzbekistan.